Kewajiban Asasi Manusia Perspektif Hukum Pidana Islam - Hamzah Hasan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
Human Rights Obligations remains a problem that is always interesting to talk about, especially in the perspective of Islamic criminal law. Human rights in Islamic criminal law become the main aspect because obligations must be fulfilled first before being able to claim the rights. If the obligation is fulfilled, then the rights of all human beings can also be fulfilled. The Islamic law has the concept that obligations are more or more priority than the rights, and this is very different from the national legal system and the Western legal system. The principle of fulfilling the obligation first than the prosecution of the rights is the nature of the law which encourages avoidance of someone committing acts that can harm others. In order to create order in life or create benefit in society, the Islamic criminal law regulates it with the concept of al-darūriyāt al-khamzah.